Effect of magnetite supplementation on mesophilic anaerobic digestion of phenol and benzoate: Methane production rate and microbial communities. (April 2022) - Jung, Sungyun; Kim, Minjae; Lee, Juyun; Shin, Juhee; Shin, Seung Gu; Lee, Joonyeob
Highlights: The effect of magnetite particles (MP) in AD of phenol and benzoate was examined. MP boosted CH4 production rate by 9.0–68.0% and shortened lag time in AD of phenol. MP significantly affected microbial community structures. Geobacter, Peptoclostridium, Methanosaeta could enhance AD by MP-mediated DIET. Abstract: Anaerobic sequential batch tests treating phenol and benzoate were conducted to evaluate the potential of magnetite supplementation to improve methanogenic degradation of phenol and benzoate, and to identify active microbial communities under each condition. Specific CH4 production rates during anaerobic digestion were 218.5 mL CH4 /g VSS/d on phenol and 517.6 mL CH4 /g VSS/d on benzoate. Magnetite supplementation significantly increased methanogenic degradation of phenol by 9.0–68.0% in CH4 production rate, and decreased lag time by 7.9–48.0%, with no significant reduction in CH4 yield. Syntrophorhabdus, Sporotomaculum, Syntrophus, Syntrophomonas, Peptoclostridium, Soehngenia, Mesotoga, Geobacter, Methanosaeta, Methanoculleus, and Methanospirillum were revealed as active microbial communities involved in anaerobic digestion of phenol and benzoate. Magnetite-mediated direct interspecies electron transfer between Geobacter, Peptoclostridium, and Methanosaeta harundinacea could contribute to this improvement.